Postoperative Cognitive Deterioration During Cardiac Surgery with Cardiopulmonary Bypass is Related to Impairments of Cerebrovascular Autoregulation. (16th November 2020) - Krakauskaite, Solventa; Petkus, Vytautas; Kumpaitiene, Birute; Svagzdiene, Milda; Sirvinskas, Edmundas; Adomaitiene, Virginija; Zakelis, Rolandas; Chomskis, Romanas; Benetis, Rimantas; Ragauskas, Arminas
Abstract: INTRODUCTION: Postoperative cognitive dysfunction (POCD) occurs during the first post-operative week in approximately 33–83% of cases. Recent clinical data shows that patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) experience episodes of cerebrovascular autoregulation (CA) impairment. This impairment is related to POCD and delirium. METHODS: The observational study of non-invasive ultrasonic volumetric CA monitoring included 59 patients without pre-operative neurological disorders undergoing elective coronary artery bypass graft surgery with CPB in Kaunas Clinics, Hospital of Lithuanian University of Health Sciences (Lithuania). All patients received a standardized anaesthetic and CPB management. All patients underwent a set of neuropsychological tests the day before and 10 days after the surgery to evaluate cognitive function. Monitoring of CA status was performed by using a non-invasive ultrasonic CA monitoring method that is based on real-time measurements of intracranial blood volume (IBV) reactions following changes in ABP. RESULTS: Twenty-two patients (37%) experienced POCD, 37 patients (63%) did not display any evidence of cognitive deterioration. The duration of the single longest CA impairment event was found reliably associated with occurrence of POCD ( P < . 05). The critical duration of the single longest CA impairment event was 5.03 minutes (odds ratio 14.5; CI 3.9-51.8) for investigated population. CONCLUSION: The performed study by using non-invasive real-time CA monitoring method for patients undergoing cardiac surgery with CPB showed that the duration of the single longest CA impairment event is reliably associated with POCD. One cause of impaired CA is mean arterial blood pressure drop below the individual lower limit of CA. The duration of the single longest CA impairment event is the risk factor that is associated with POCD.